Visible photoluminescence at room temperature from a-Si : H films grown by ultrahigh vacuum electron cyclotron resonance chemical vapor deposition - Joo, SJ; Lim, SH; Yoon, E; Choi, WC; Kim, EK; Marra, DC; Aydil, ES (KOREAN PHYSICAL SOC, 1999)
Hydrogenated amorphous Si (a-Si:H) films were grown without external heating by ultrahigh vacuum electron cyclotron resonance chemical vapor deposition (UHV-ECRCVD) and structural/optical properties were characterized. Visible red photoluminescence (PL), centered around the wavelengths of similar to 700 nm, is obtained from the as-grown samples at room temperature. Strong oscillation of PL spectra is observed in the films grown on oxidized Si substrates, which is believed to originate from Fabry-Perot interference effect. As-grown a-Si:H films do not contain Si nanocrystals, and a large amount of (SiH2)(n)(polysilane) bonding is found. PL intensity depends on deposition conditions, but it usually becomes stronger as the polysilane-content in the as-grown film increases. When the samples are annealed at 350 degrees C, integrated PL intensity is quenched almost completely as the polysilane content falls off abruptly. Based on these results, possible luminescence mechanisms are discussed.
Keywords: POROUS SILICON; NANOCRYSTALLINE SILICON; POLYSILANE ALLOYS; LIGHT-EMISSION; LUMINESCENCE; MECHANISM; LAYERS; OXIDE